Effect of agricultural credit on farmer's income and factors affecting credit demand and access focus on golestan province in Iran - Abyar, Noormohammad (2010)
Credit is important in addressing farmers'financial constraints. Iran has been implementing a long-standing agricultural credit policy in order to reduce rural poverty and improve farmer's income improvement but there are some problems related to credit income impacts and factors affecting demand and access to credit. This study aims to determine the agricultural credit's effect on farmers' income and its demand and access determinants. Econometrics tools were utilized (e.g., income and demand functions, and analysis of survey data collected from farmers who availed of agricultural bank credit in Golestan province in north of Iran). Results showed that: 1) credit had significant effect on farmers' income; 2) farm size and farmer's age are determinants of credit demand quantity; and 3) farm size, farmer's asset, age, and nonfarm income perform important roles in access to agriculture bank credit. This latter result implies that older farmers with larger farms and who had nonfarm income and more assets gained more access to credit that other farmers.
Keywords: Credit; Rural credit